On N. N. Bogolyubov's works in classical and quantum statistical mechanics - Mitropolskiy, Yu. A.; Petrina, D. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A review of N. N. Bogolyubov's works in classical and quantum statistical mechanics is presented.